(untitled) (Voice of Teacher, 2024)
The tourism industry in Nepal is endowed with a lot of natural beauty and cultural heritage that has a great economic potential in the economic development of Nepal. The paper discusses the correlation between tourism and economic growth in Nepal based on Barro growth regression and ARDL model based on time series data (1975-2023). The result reveals that a short-run positive impact of tourist arrivals on GDP is observed, whereas foreign exchange earnings on tourism are not significantly related to growth. The low rate of adjustments indicates low long-run effects. The findings are not congruent with the tourism-led growth hypothesis, signifying that Nepal has not used the full potential of tourism in relation to its economic benefits. The policies need to target greater expenditure and stay by tourists.